2017
DOI: 10.1007/s11695-017-2760-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-Trocar Sleeve Gastrectomy vs Standard Five-Trocar Technique: a Randomized Controlled Trial

Abstract: researchregistry2386.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The technique is particularly attractive for the placement of an adjustable gastric band, which requires an incision large enough to insert the band and the port, and for the sleeve gastrectomy to allow retrieval of the gastric specimen. [5][6][7][8][9][10] To the best of our knowledge, this is one of the first clinical trials that assessed the feasibility of three port technique in laparoscopic mini-gastric bypass and various revisional bariatric surgeries (56 underwent mini-gastric bypass, 3 underwent R/Y gastric bypass, 2 underwent SASI, 11 patients post VBG revision to gastric bypass, 3 patients post sleeve gastrectomy revision to mini-gastric bypass, 2 patients post gastric band revision to mini-gastric bypass and 1 patient post plication revision to R/Y gastric bypass).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is particularly attractive for the placement of an adjustable gastric band, which requires an incision large enough to insert the band and the port, and for the sleeve gastrectomy to allow retrieval of the gastric specimen. [5][6][7][8][9][10] To the best of our knowledge, this is one of the first clinical trials that assessed the feasibility of three port technique in laparoscopic mini-gastric bypass and various revisional bariatric surgeries (56 underwent mini-gastric bypass, 3 underwent R/Y gastric bypass, 2 underwent SASI, 11 patients post VBG revision to gastric bypass, 3 patients post sleeve gastrectomy revision to mini-gastric bypass, 2 patients post gastric band revision to mini-gastric bypass and 1 patient post plication revision to R/Y gastric bypass).…”
Section: Discussionmentioning
confidence: 99%
“…Vincenzo Consalvo et al 11 conducted a study comparing perioperative outcomes of RPLSG versus conventional multi-port LSG. This study found a significant difference in the mean operative time between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Sleeve gastrectomy (SG) is the most popular bariatric procedure worldwide [1] because of weight loss maintenance and acceptable morbidity [2,3]. Reduced port 5 SG (i.e three trocars) has emerged has a new standard providing comparable safety and efficacy [4,5] as compared to the five port technique. However liver retraction and incisional hernia remain unresolved issues [6].…”
Section: Introductionmentioning
confidence: 99%